1996
DOI: 10.1126/science.274.5294.1891
|View full text |Cite
|
Sign up to set email alerts
|

Tomography of the Source Area of the 1995 Kobe Earthquake: Evidence for Fluids at the Hypocenter?

Abstract: Seismic tomography revealed a low seismic velocity (-5%) and high Poisson's ratio (+6%) anomaly covering about 300 square kilometers at the hypocenter of the 17 January 1995, magnitude 7.2, Kobe earthquake in Japan. This anomaly may be due to an overpressurized, fluid-filled, fractured rock matrix that contributed to the initiation of the Kobe earthquake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
203
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 344 publications
(224 citation statements)
references
References 23 publications
17
203
1
3
Order By: Relevance
“…This is consistent with the suggestions of Benloft [1951] that the existence of aftershocks is related to a stress anomaly that dies away due to viscoelastic creep. The stress rotation might imply the existence of inelastic processes in the rupture zone, e.g., fluids [Johnson and McEvilly, 1995;Zhao et al, 1996]. The theory of Benloft [1951] only shows a change in stress magnitudes, not a rotation of the principal axes as observed during the Coalinga, Landers, and Northridge sequences.…”
Section: This Difference (2 •) Is Insignificant Since the Er-mentioning
confidence: 99%
“…This is consistent with the suggestions of Benloft [1951] that the existence of aftershocks is related to a stress anomaly that dies away due to viscoelastic creep. The stress rotation might imply the existence of inelastic processes in the rupture zone, e.g., fluids [Johnson and McEvilly, 1995;Zhao et al, 1996]. The theory of Benloft [1951] only shows a change in stress magnitudes, not a rotation of the principal axes as observed during the Coalinga, Landers, and Northridge sequences.…”
Section: This Difference (2 •) Is Insignificant Since the Er-mentioning
confidence: 99%
“…One of the distinct features of the Kobe earthquake is that fluids were involved in the rupture nucleation as evidenced by numerous observations [see Zhao and Negishi, 1998 for a detailed review]. A highresolution tomographic study revealed that the Kobe mainshock hypocenter is located in a distinctive zone characterized by low P and $ wave velocities and a high Poisson's ratio [Zhao et al, 1996;Zhao and Negishi, 1998]. The anomalous zone exists in the depth range of 16 to 21 km and extends 15 to 20 km laterally, and is interpreted as a fluid-filled, fractured rock matrix that contributed to the initiation of the Kobe earthquake [Zhao and Negishi, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…One plausible explanation is the existence of anhydrous plutonic rocks in this region (Yoshida, 2001), however, this interpretation needs further investigation. The presence of partial melt or fluids beneath the seismogenic zone in the lower crust structure can change the deformation of the fault zone and affect its stress accumulation (Zhao et al, 1996;Hasegawa et al, 2000Hasegawa et al, , 2005Nakajima et al, 2006).…”
Section: Interpretationsmentioning
confidence: 99%
“…For example, Zhao et al (1996) reported a low seismic velocity and a high Poisson's ratio anomaly around the hypocenter of the 1995 Kobe earthquake. They showed that this anomaly may be due to high pore fluid pressure and a fluid-filled, fractured rock matrix near the bottom of the seismogenic layer that contributed to the initiation of the Kobe earthquake.…”
Section: Introductionmentioning
confidence: 99%